2017
DOI: 10.1259/bjr.20160885
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic insufficiency fracture (PIF) incidence in patients treated with intensity-modulated radiation therapy (IMRT) for gynaecological or anal cancer: single-institution experience and review of the literature

Abstract: Objective: To summarize the results of pelvic insufficiency fracture (PIF) incidence in patients with anal or gynaecological cancer treated by pelvic intensitymodulated radiation therapy (IMRT). Methods: The clinical and morphological (CT and/or pelvic MRI) characteristics of patients treated by IMRT at our institution between 2007 and 2014 were analyzed. The global incidence of PIF after external beam radiotherapy and the impact of tumour site (gynaecological or anal cancer) were determined. A dosimetric stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 42 publications
(57 reference statements)
2
36
2
Order By: Relevance
“…Aging is also an important risk factor. A higher pelvic fracture risk after RT has been reported in many different studies in patients who are older than 50, 55, 60, 65, or 70 . Our study also proved that in a multivariable Cox model, patients older than 60 years had a higher pelvic fracture risk (HR: 1.086, CI: 1.076‐1.097, P < 0.001).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Aging is also an important risk factor. A higher pelvic fracture risk after RT has been reported in many different studies in patients who are older than 50, 55, 60, 65, or 70 . Our study also proved that in a multivariable Cox model, patients older than 60 years had a higher pelvic fracture risk (HR: 1.086, CI: 1.076‐1.097, P < 0.001).…”
Section: Discussionsupporting
confidence: 85%
“…One study reported that the reduction rate in volumetric bone mineral density among patients who received C/T after 1 year was 15.9% over the L1‐L2 spine and 10.4% over the femoral neck . However, C/T was not a significant risk factor for pelvic fracture in several studies . Combining C/T with RT may cause a higher pelvic fracture rate based on a study of gynecology malignancy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore essential to distinguish radiation-induced fractures from metastases, which may require biopsies and initiation of treatments such as chemotherapy. These two lesions can generally be distinguished by alternately performing pelvic CT and MRI follow-ups [9]. MRIs can detect early changes of sacral insufficiency with a proved sensitivity at or near 100%.…”
Section: Discussionmentioning
confidence: 99%
“…8). 15,16 In this situation, both CT and MRI can be diagnostic showing the fractures in the absence of true bone destruction. Vascular malignancies such as epithelioid hemangioendothelioma and angiosarcoma of bone can be multifocal in up to two thirds of cases simulating metastatic disease.…”
Section: Commandment 7: Not All Multiple Bone Lesions Are Metastases mentioning
confidence: 99%